Antifibrosis treatment by inhibition of VEGF, FGF, and PDGF receptors improves bladder wall remodeling and detrusor overactivity in association with modulation of C‐fiber afferent activity in mice with spinal cord injury. Issue 6 (20th May 2021) - Kwon, Joonbeom; Lee, Eun‐Ju; Cho, Hyun‐Jung; Jang, Ji‐Ae; Han, Min‐Su; Kwak, Eunkyoung; Kim, Haesoo; An, Jihyun; Park, Donghwi; Han, Seungwoo; Shimizu, Nobutaka; Suzuki, Takahisa; et al.
Abstract: Aims: Spinal cord injury (SCI) above the sacral level causes bladder dysfunction and remodeling with fibrosis. This study examined the antifibrotic effects using nintedanib, an inhibitor of vascular endothelial growth factor, fibroblast growth factor, and platelet‐derived growth factor receptors, on detrusor overactivity (DO) and bladder fibrosis, as well as the modulation mechanisms of C‐fiber afferent pathways. Methods: Thirty female C57BL/6 mice were divided into group A (spinal intact), group B (SCI with vehicle), and group C (SCI with nintedanib). At 2 weeks after SCI, vehicle or 50 mg/kg nintedanib was administered subcutaneously for 2 weeks. Then, cystometry was conducted, followed by RT‐PCR measurements of fibrosis‐related molecules, muscarinic, β‐adrenergic, TRP and purinergic receptors in the bladder or L6‐S1 dorsal root ganglia (DRG). Trichrome stain and Western blot analysis of transforming growth factor‐beta and fibronectin were performed in the bladder. TRPV1 expression in L6 DRG was measured by immunohistochemistry. Results: In cystometry, intercontraction intervals, nonvoiding contractions, voided volume, and voiding efficiency were significantly improved in group C versus group B. RT‐PCR, Western blotting, and trichrome staining revealed the fibrotic changes in the bladder of group B, which was improved in group C. Increased messenger RNA levels of TRPV1, TRPA1, P2X2, and P2X3 in DRG of group B were significantly decreased in group C. TRPV1 immunoreactivity in DRG was increased in group B, but decreased in group C. Conclusions: Nintedanib improves storage and voiding dysfunctions and bladder fibrosis in SCI mice. Also, nintedanib‐induced improvement of DO is associated with reduced expression of C‐fiber afferent markers, suggesting the modulation of bladder C‐fiber afferent activity.